Late Quaternary Marine and Terrestrial Environments, Northwestern Baffin Island, Northwest Territories - Short, Susan; Andrews, John; Williams, Kerstin; Weiner, Nancy; Elias, Scott (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1994)
ABSTRACTPaleoenvironmental data were analyzed from terrestrial, lake, and marine sediments collected near Arctic Bay, Baffin Island, N.W.T. Eighteen new radiocarbon dates provide chronological control, superseding earlier results. Spuriously old dates were obtained from both sandy peats and low-organic lake sediments. The most reliable dates were from marine shells and foraminifera. They indicate that déglaciation was underway by 9000 BP rather than 16,000 BP. Over the period of the record, the local environment was characterized by a high arctic pollen assemblage dominated by grass, sedge, and willow; a middle Holocene warm period is indicated by increased willow, herb, and moss values. Sea-ice conditions were severe enough to inhibit the growth of diatoms until ca. 6300 BP and ice proximal and deglacial conditions prevailed in the fiords until ca. 6000 BP. Diatom productivity increased between 3000 BP and 2500 BP, suggesting warmer surface waters and less sea ice. After 2000 BP diatom accumulation decreased sharply, due to a cooling of climate. The foraminifera indicate a major change in bottom water conditions ca. 4000 BP as the benthic species shift from a calcareous to an arenaceous assemblage.